ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KAYU CEMPAKA PADA INDUSTRI MEBEL DENGAN MENGGUNAKAN METODE EOQ (Studi Kasus Pada UD. Batu Zaman) - Mutiara Simbar; Theodora M. Katiandagho; Tommy F. Lolowang; Jenny Baroleh (Universitas Sam Ratulangi, 2014)
ABSTRACTMutiara Simbar. Analysis of â€œCempakaâ€ Raw Material Inventory Control In Wood Furniture Industry Using EOQMethod (Case Studies at â€œUD. Batu Zamanâ€), Under the guidance of Theodora M. Katiandagho as a Chairman, Tommy Lolowang and Jenny Baroleh as Members.The objective of this research are, a)analyze the optimum volume of raw materials required by â€œUD. Batu zamanâ€ for 2013period, b)analyze the total cost of raw material supply cempaka to be incurred by UD. Batu Zaman for 2013period, c)analyzetime to re-ordering of raw materials cempaka by UD. Batu Zaman for 2013period, d)analyze the amount of safety stock cempaka timber must be provided by UD. Batu Zaman per period in 2013, and e)analyze the inventory control of raw materials Cempaka wood in the furniture industry by using EOQ (Case Studies at UD. Batu zaman).Data was collected from April 2014 - September 2014, The data obtained were primary data and secondary data, Primary data were data collected directly from the company . Secondary data were data that has been arranged in the form of written documents obtained from the company , previous literature as well as from the Internet. Analysis data based on